Choosing Peace and Order: National Security and Sovereignty in a North American Borderland, 1837–42. Issue 5 (19th October 2016) - Lacroix, Patrick
Abstract : This article considers the international ramifications of the Canadian Rebellions of 1837, in particular their impact on US politics and policy-making as well as on the state of the international border. The Rebellions and the ensuing border raids led to the deployment of US and British forces in the borderlands, not in pursuit of war but in the interest of peace. Ignoring popular agitation in the Canadian colonies and in border states, the British and US governments expressed their commitment to peace and recognised that continued friendly relations required further assertion of central state authority on both sides of the boundary line. Thus, the events of 1837–42 mark an important advance in the development of national security and national sovereignty in North America. This paper expands upon purely national depictions of the Canadian Rebellions and integrates international developments by utilising a borderlands approach and traditional diplomatic history.